TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN LOCAL GOVERNMENT AGENCIES - Idris, Julizar (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This investigation's objective is to determine the extent to which transformational leadership impacts the quality of public services provided by local government agencies. Interviews and observations are employed to gather data qualitatively. The study results indicate that transformational leadership can increase employee motivation, create a collaborative organizational culture, and improve communication between employees. Leaders who implement this leadership style successfully motivate employees to participate in decision-making and achieve excellence, enhancing public service quality and responsiveness. However, challenges in consistently applying transformational leadership must be overcome through training and developing leadership skills. These findings are anticipated to guide local government agencies in enhancing the quality of public services via effective leadership.